FAKTOR-FAKTOR PENENTU PENINGKATAN KINERJA PENYULUH PERTANIAN DALAM MEMBERDAYAKAN PETANI (Kasus di Kabupaten Kampar Provinsi Riau) - Marliati Marliati; Sumardjo Sumardjo; Pang S. Asngari; Prabowo Tjitropranoto; Asep Saefuddin (Jurnal Penyuluhan, 2008)
The agriculture extension program can be developed effectively and efficiently by professional personal in agriculture extension field. The existing main problem is low quality and quantity of agri-extension workers (include in Kampar district, Riau province). Therefore, the goals of this research are: (1) To analyze: farmer characteristics; social system characteistics; agri-extension worker competencies; agri-extension worker performance to empower farmer and level of fulfill need for farmer’s capacity development in agribusiness; (2) To analyze determinant factors which influenze agri-extension worker performance to empowering farmer and (3) To formulate strategy to increase agri-extension worker performance to empower farmer. Through multistage cluster sampling technique, this research have found farmers sample with 180 person amoun (each of them consist of: 60 food crops farmers, 60 oil palm farmers and 60 rubber farmers). This research have been done from June 2007 up to October 2007. The analysis of data done by descriptive analysis and Path analysis. The research conclusion are: performance level of agri-extension worker to empower farmer still not yet good (“enough” category) because of the influence factor to the performance of agri-extension worker: agri-extension worker competencies (communication competency; competency in farmers learning and competency in social interaction); farmer characteristics ( farmer’s access to the non formal education) and social sistem support (soscio-cultural values; agribusiness facilitation by government institution and fartmer’s access to the aggribusiness institution) are still not yet (“enough” category).